A Nietzschean tafsīr for Nazi Germany: The Commentary to Sadr-ud-Dīn’s Qur’an of 1939 - Jonker, Gerdientje (Journal of Qur'anic Studies, 2024)
This contribution traces the history of the German Qur'an edition published by the Ahmadiyya Anjuman Isha’at-e-Islam Lahore (Lahore-Ahmadiyya) in Berlin in 1939. Maulvi Sadr-ud-Dīn, the Lahore-Ahmadiyya missionary who erected the first mosque in Berlin, fashioned the translation. To reach out to a German audience gearing up for war, he entrusted his Berlin collaborator, the philosopher Hugo Marcus, with the details of the commentary. The narrative starts in 1924, when Tatar intellectuals first sat down with Sadr-ud-Dīn to discuss the necessity of preparing Qur'an editions for European readers. It ends with the publication of the German Qur'an at the moment Germans were finalising their war preparations. Hugo Marcus’ approach to his commentary involved relating single Qur'an verses to Friedrich Nietzsche's philosophy, focusing on genius, heroism, and suffering. In making that choice, he connected the Qur'anic text to the Herrenethik (‘ethics of male superiority’) that pervaded National-Socialist (Nazi) ideology. From this emerged an exegesis full of delusions about masculinity and racist arrogance. A comparison with Hugo Marcus’ writings of the 1930s illustrates how it was wrought. In their approach to racism, nationalism, and war, Ahmadi Muslim missionaries and German Muslims in Berlin differed considerably. In their many attempts to bridge East and West through religion, their disagreements on these issues present a pivotal moment in intercultural communication, leaving an imprint on how the Qur'an was explained in Sadr-ud-Dīn's translation. Whereas the Lahore-Ahmadiyya tried to smooth the way towards an ‘international religion’ and defended the ‘Jihad of the Pen’, German Muslims steered close to the expectations of a frenzied, war-minded public. A straightforward document, Hugo Marcus’ tafsīr served to exonerate them in advance, wherever they were heading.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Friedrich Nietzsche; Hugo Marcus; Lahore-Ahmadiyya; Nazi Germany; rationalist Islam; Sadr-ud-Dīn; tadjdīd; Tatar Reformers